Diapycnal mixing and the internal wave field north of the Kerguelen Plateau - Amelie Meyer (2014)
Dissipating internal waves are the main source of mixing in the stratified ocean. Recent observational and modelling studies in the Southern Ocean primarily associate the generation of internal waves with either wind forcing or with rough topography. This work explores the nature of mixing and its sources north of the Kerguelen Plateau, a large topographic feature in the Southern Ocean. Based on novel observations, we present the distribution and intensity of mixing, and the internal wave field properties. This thesis includes (i) a regional description of the Kerguelen Plateau oceanographic characteristics; (ii) estimates of mixing and its sources; and (iii) a study of the internal wave field in the vicinity of the Plateau. The data consist of 914 temperature, salinity, pressure and horizontal velocity profiles from Electromagnetic Autonomous Profiling Explorer (EM-APEX) floats deployed northeast of the Kerguelen Plateau in 2008. We are able to estimate diapycnal mixing in the upper 1600m of the water column. To estimate mixing, we apply both a Thorpe-scale analysis on density inversions and a shear-strain parameterization method and compare the estimates with direct microstructure measurements.